Marketing Research on Passenger Satisfaction With Public Transport Service in the City of Belgrade - Radnović, Branislav; Marić, Radenko Miloš; Radnović, Vladana; Ilić, Milena; Lukač, Dragan (Promet - Traffic&Transportation, 2015)
The aim of this paper is to determine, based on conducted marketing research, the level of passenger satisfaction with public transport services for the purpose of making better marketing decisions in the example of the City of Belgrade. The main task is to test the hypothesis on the existence of significant influence of factors, such as quality service, attitude and behaviour of employees (e.g. driver), adequate informing, quality of vehicles, line routes and timetable, on passenger satisfaction. Correlation coefficient and regression analysis were used for interpreting the obtained results and examining the formulated hypothesis. Empirical research has shown that there is a significant correlation between the aforementioned factors and passenger satisfaction with public transport services. The obtained results provided recommendations and guidelines for improving and increasing the quality of public transport services. The research results also provide the basis for future research that could examine the relationship between passenger satisfaction with services and sub-groups within the analyzed factors.